Immunological risk factors for sepsis-associated delirium and mortality in ICU patients - Lei, Wen; Ren, Zhiyao; Su, Jun; Zheng, Xinglong; Gao, Lijuan; Xu, Yudai; Deng, Jieping; Xiao, Chanchan; Sheng, Shuai; Cheng, Yu; Ma, Tianshun; Liu, Yu; et al. (Frontiers in Immunology, 2022)
Background A major challenge in intervention of critical patients, especially sepsis-associated delirium (SAD) intervention, is the lack of predictive risk factors. As sepsis and SAD are heavily entangled with inflammatory and immunological processes, to identify the risk factors of SAD and mortality in the intensive care unit (ICU) and determine the underlying molecular mechanisms, the peripheral immune profiles of patients in the ICU were characterized. Methods This study contains a cohort of 52 critical patients who were admitted to the ICU of the First Affiliated Hospital of Jinan University. Comorbidity, including sepsis and SAD, of this cohort was diagnosed and recorded. Furthermore, peripheral blood samples were collected on days 1, 3, and 5 of admission for peripheral immune profiling with blood routine examination, flow cytometry, ELISA, RNA-seq, and qPCR. Results The patients with SAD had higher mortality during ICU admission and within 28 days of discharge. Compared with survivors, nonsurvivors had higher neutrophilic granulocyte percentage, higher CRP concentration, lower monocyte count, lower monocyte percentage, lower C3 complement level, higher CD14loCD16+ monocytes percentage, and higher levels of IL-6 and TNFα. The CD14hiCD16- monocyte percentage manifested favorable prediction values for the occurrence of SAD. Differentially expressed genes between the nonsurvival and survival groups were mainly associated with immune response and metabolism process. The longitudinal expression pattern of SLC2A1 and STIMATE were different between nonsurvivors and survivors, which were validated by qPCR. Conclusions Nonsurvival critical patients have a distinct immune profile when compared with survival patients. CD14hiCD16- monocyte prevalence and expression levels of SLC2A1 and STIMATE may be predictors of SAD and 28-day mortality in ICU patients.